2002
DOI: 10.1007/s00438-001-0609-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the Antifungal Protein in Aspergillus giganteus

Abstract: Regulation of the expression of the afp gene that codes for the Antifungal Protein of Aspergillus giganteus was investigated using a reporter system. For this purpose, the E. coli reporter gene uidA encoding beta-glucuronidase (GUS) was placed under the control of the afp promoter. No homologous integration of the reporter construct into the afp site was observed among 156 transformants tested. In one of the transformants carrying a single, ectopically integrated, copy of the construct, GUS and AFP both displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 37 publications
3
29
0
1
Order By: Relevance
“…Ribosomally synthesized antifungal peptides of the AFP family are promising molecules for use in medical or agricultural applications to combat humanand plant-pathogenic fungi (40). We and others could show that expression of their cognate genes are under tight temporal and spatial regulation in their native hosts and precedes asexual sporulation (24,(41)(42)(43).…”
Section: Co-expression Resources Accurately Predict Transcription Facmentioning
confidence: 98%
“…Ribosomally synthesized antifungal peptides of the AFP family are promising molecules for use in medical or agricultural applications to combat humanand plant-pathogenic fungi (40). We and others could show that expression of their cognate genes are under tight temporal and spatial regulation in their native hosts and precedes asexual sporulation (24,(41)(42)(43).…”
Section: Co-expression Resources Accurately Predict Transcription Facmentioning
confidence: 98%
“…The P. chrysogenum paf and the A. giganteus afp exhibit a temporal and spatial regulation during asexual differentiation (Hegedus et al. , 2011a; Meyer et al. , 2002).…”
Section: Amps Of Fungal Originmentioning
confidence: 99%
“…No gene expression occurs in conidiophores or conidia (Hegedus et al. , 2011a; Meyer, 2008; Meyer et al. , 2002).…”
Section: Amps Of Fungal Originmentioning
confidence: 99%
“…Upstream regulatory regions of gluc78 (which encodes GLUC78, a 78-kDa exo-1,3-glucosidase) (Donzelli et al, 2001), ech42 and nag1 (which encodes CHIT73, a 73-kDa N-acetylhexosaminidase) (Peterbauer et al, 1996) from T. atroviride contain clustered putative binding sites, such as GATA, stress response elements, BrlA response elements and AbaA response elements, suggesting that they are regulated by a number of stimuli. A study showed that complex response elements existing in the promoter region of the Antarctosaurus giganteus AFP gene (encoded a antifungal protein) are responsible for its efficient transcription in its expression vectors (Meyer et al, 2002).…”
Section: The Use Of Strong Promoters In Desired Genementioning
confidence: 99%